2022
DOI: 10.1093/jaoacint/qsac092
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Spectrophotometric Resolution Techniques for a Spectrally Overlapping Spasmolytic Binary Mixture along with Dichloroaniline as a Toxic Impurity: Application to Content Uniformity Testing

Abstract: Background Irritable bowel syndrome (IBS) is considered an anxious disease leading to undesirable pain. Phloroglucinol (PHG) and Trimethylphloroglucinol (TMG) are co-formulated as spasmolytic medication that is considered to be effective in reducing smooth muscle spasm. Dichloroaniline (DCL) is a specified PHG pharmacopoeial impurity which is needed to be monitored to avoid its toxic effects. Objective Different smart approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the statistical study of spectra, PLS and PCR algorithms are frequently employed to extract detailed data from more general data [ 26 , 27 ]. The PLS and PCR algorithms simultaneously consider the data about replies and levels [ 28 , 29 ]. The leave one out cross-validation method was used in this research to determine the appropriate number of components by excluding one sample at a time.…”
Section: Resultsmentioning
confidence: 99%
“…In the statistical study of spectra, PLS and PCR algorithms are frequently employed to extract detailed data from more general data [ 26 , 27 ]. The PLS and PCR algorithms simultaneously consider the data about replies and levels [ 28 , 29 ]. The leave one out cross-validation method was used in this research to determine the appropriate number of components by excluding one sample at a time.…”
Section: Resultsmentioning
confidence: 99%
“…For PHG, TMG, and DCL, respectively, the suggested chemometric models were applied in the ranges of 6.0-14.0, 5.0-25.0, and 2.0-10.0 g/mL. The presented techniques were successful in determining the pharmaceutical dosage forms of the specified medications and determining the consistency of dosage units' contents (45).…”
Section: Spectrophotometric Methodsmentioning
confidence: 99%
“…Autonomic nerves innervate visceral smooth muscle, and pain may occur due to spasms of visceral smooth muscle. Several studies demonstrated that visceral smooth muscle spasms are caused by abnormalities in the sympathetic nerves that mediate them, leading to abdominal pain, chest pain, and urinary pain [ 30 ]. Therefore, the sympathetic nerve mediates the occurrence of immune abnormalities and may cause the abnormal spasm of smooth muscle to produce pain.…”
Section: Autonomic Nervous System Regulation Of Inflammation Pain And...mentioning
confidence: 99%